Osmium-catalyzed oxidative cyclization of dienes and their derivatives. - Pilgrim, B; Donohoe, T (2013)
The development and application of novel methods for accomplishing the synthesis of heterocycles via osmium-catalyzed oxidative cyclization onto an alkene is described in this Perspective. Beginning with a fortuitous discovery, an extensive examination of the possible mechanism of cyclization has been carried out, and the method was continuously developed until it had been transformed into an extremely efficient and powerful new catalytic reaction for the formation of tetrahydrofurans and pyrrolidines with complete control over all aspects of relative and absolute stereochemistry. By working with Os(VI) rather than the more familiar Os(VIII), a highly potent yet mild set of reaction conditions were developed. In addition to the method development studies, this work also sets out some synthetic challenges against which the methodology was tested. Pleasingly, the catalytic oxidative cyclization has proved itself to be an efficient and functional group tolerant process that was pivotal to the completion of several natural product syntheses.